La transtextualité et la transposition d’art comme outils d’étude de l’ekphrasis : l’exemple de Percy Bysshe Shelley - Fabien Desset (Itinéraires)
Although Gerard Genette has qualms about a ‘transaesthetic study’ in Palimpsests (trans. 1997), mainly due to the difference of the two semiotic systems, his transtextuality offers a series of thematic and formal transformations that can show how a work of art is recast, once it is considered as made up of various elements that can for instance be suppressed, developed or transposed into another diegetic context. Some critics have gone further in studying what they call pictorialism or art transposition, which Mark Eigeldinger defines as writing in the manner of painting or sculpting, thanks to sense and sound effects. This paper will thus introduce, synthesise and formalise those two complementary critical tools, by focusing on Percy Bysshe Shelley, who already considered the transaesthetic character of his poetry when he described his brain as the ‘portfolio’ of works of art seen in Italy.